Microwave-Frequency Experiment Validation of a Novel Magneto-Photonic Crystals Circulator - Yong Wang; Dengguo Zhang; Shixiang Xu; Biaogang Xu; Zheng Dong; Quan Xue (IEEE Photonics Journal)
A novel three-port Y-shaped circulator based on magneto-photonic crystals is first experimentally investigated. The band gaps of TE mode for the photonic crystals are calculated by plane wave expansion method. The transmission characteristics of the circulator are simulated by finite element method and the experiments are performed in the microwave regime. At the central frequency of 9.83 GHz, the optimal experimental isolation of –61.11 dB is better than the numerical results.